2022
DOI: 10.5114/wiitm.2022.118799
|View full text |Cite
|
Sign up to set email alerts
|

The importance of inflammatory markers in detection of complications in patients with gastric cancer undergoing the Enhanced Recovery After Surgery (ERAS) protocol: a prospective cohort study.

Abstract: Introduction: Early diagnosis reduces mortality and morbidity rates in gastrointestinal system (GIS) anastomoses. Aim:The aim of the present study was to investigate the importance of some substances that were used to detect major complications early in patients who were treated in line with the Enhanced Recovery After Surgery (ERAS) protocol for gastric cancer. Factors included in the study were , tumor necrosis factor-α (TNF-α), C-reactive protein (CRP), procalcitonin (PCT) and white blood cell (WBC).Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In our study, we applied a more extensive search strategy to investigate the effects of specific nutrient substances, including Arg, Gln, ω-3-FAs, and RNA, on the application of enhanced immunonutrition (EIN) compared to standard EN. Our findings indicate that EIN significantly enhances the post-operative levels of serum protein and immunological parameters, as shown by a significant standardized mean difference [51] presented findings indicating that timely identification of gastrointestinal system (GIS) anastomosis-related issues contributes to decreased mortality and morbidity rates. Additionally, the authors suggested that the supplementation of interleukin-1β (IL-1β), tumour necrosis factor-a (TNF-a), C-reactive protein (CRP), and procalcitonin (PCT) may serve as a viable approach for the early detection of significant issues in gastric cancer patients who are undergoing the Enhanced Recovery After Surgery (ERAS) protocol.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In our study, we applied a more extensive search strategy to investigate the effects of specific nutrient substances, including Arg, Gln, ω-3-FAs, and RNA, on the application of enhanced immunonutrition (EIN) compared to standard EN. Our findings indicate that EIN significantly enhances the post-operative levels of serum protein and immunological parameters, as shown by a significant standardized mean difference [51] presented findings indicating that timely identification of gastrointestinal system (GIS) anastomosis-related issues contributes to decreased mortality and morbidity rates. Additionally, the authors suggested that the supplementation of interleukin-1β (IL-1β), tumour necrosis factor-a (TNF-a), C-reactive protein (CRP), and procalcitonin (PCT) may serve as a viable approach for the early detection of significant issues in gastric cancer patients who are undergoing the Enhanced Recovery After Surgery (ERAS) protocol.…”
Section: Discussionmentioning
confidence: 55%
“…All the observed outcomes exhibited statistical significance ( p < 0.05), indicating a preference for the utilization of EIN in patients with gastric cancer who have gastrectomy, in comparison to EN. In their study, Gumusoglu et al (2022) [ 51 ] presented findings indicating that timely identification of gastrointestinal system (GIS) anastomosis-related issues contributes to decreased mortality and morbidity rates. Additionally, the authors suggested that the supplementation of interleukin-1β (IL-1β), tumour necrosis factor-α (TNF-α), C-reactive protein (CRP), and procalcitonin (PCT) may serve as a viable approach for the early detection of significant issues in gastric cancer patients who are undergoing the Enhanced Recovery After Surgery (ERAS) protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They mainly include proteins, enzymes, genes, antigens, and hormones produced by tumor cells or surrounding tissues, which can be detected in the blood, urine, tissue, and other body fluids[ 17 ]. Tumor markers have important clinical applications in many areas, such as early screening, diagnosis, efficacy monitoring, and prognosis evaluation[ 18 ]. CA19-9 is a glycoprotein tumor marker present in trace amounts or absent in healthy people.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a study by Gumusoglu et al [ 54 ] suggested that interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), C-reactive protein (CRP), and procalcitonin (PCT) have demonstrated potential as biomarkers for the timely identification of significant complications in gastric cancer patients who are undergoing the ERAS protocol. Imaging modalities ought to be employed in individuals exhibiting elevated concentrations of these inflammatory biomarkers on the third and fifth postoperative day.…”
Section: Discussionmentioning
confidence: 99%